2021
DOI: 10.1073/pnas.2017418118
|View full text |Cite
|
Sign up to set email alerts
|

A backward-spinning star with two coplanar planets

Abstract: It is widely assumed that a star and its protoplanetary disk are initially aligned, with the stellar equator parallel to the disk plane. When observations reveal a misalignment between stellar rotation and the orbital motion of a planet, the usual interpretation is that the initial alignment was upset by gravitational perturbations that took place after planet formation. Most of the previously known misalignments involve isolated hot Jupiters, for which planet–planet scattering or secular effects from a wider-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 34 publications
(20 reference statements)
0
46
0
Order By: Relevance
“…In this case, the inner planets may be misaligned with the stellar spin when they formed. Hjorth et al (2021) found two coplanar transiting planets' orbits are retrograde with respect to the host star (K2-290A) in a triple system, indicating the protoplanetary disk was misaligned due to perturbations from the neighboring star. Spalding & Batygin (2014) and Spalding & Millholland (2020) argue that the quadrupolar gravitational potential of a tilted, rapidly rotating host star would torque the orbits of close-in planets.…”
Section: Possible Mechanisms To Cause the Spin-orbit Misalignmentmentioning
confidence: 95%
“…In this case, the inner planets may be misaligned with the stellar spin when they formed. Hjorth et al (2021) found two coplanar transiting planets' orbits are retrograde with respect to the host star (K2-290A) in a triple system, indicating the protoplanetary disk was misaligned due to perturbations from the neighboring star. Spalding & Batygin (2014) and Spalding & Millholland (2020) argue that the quadrupolar gravitational potential of a tilted, rapidly rotating host star would torque the orbits of close-in planets.…”
Section: Possible Mechanisms To Cause the Spin-orbit Misalignmentmentioning
confidence: 95%
“…157) The further detection of a backward-spinning star with two coplanar planets is also reported. 158) These findings add constraints on the formation scenario of planetary systems.…”
Section: Imaging Exoplanetsmentioning
confidence: 85%
“…The RM effect helps to shed light onto the dynamical history of the system, as mechanisms such as planet-disk interactions help to preserve the initial spinorbit alignment, while planet-planet interactions promote misalignment (e.g., Chatterjee et al 2008;Deeg et al 2009;Storch et al 2017). The number of multi-planet systems with measured obliquities remains small (e.g., Hjorth et al 2021;Dalal et al 2019). We estimate the RM effect to be 3.71 +0.89 −0.74 m s −1 and 9.56 +2.65 −2.7 m s −1 for HD 152843 b and c, respectively (Winn 2010).…”
Section: Rossiter-mclaughlin Effect Prospectsmentioning
confidence: 99%